The Effect of Digital Transformational Leadership, Creative Self-Efficacy on Innovative Behaviour Mediated by Perceived Organizational Support - Susanti, Susanti; Ardi, Ardi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The Covid-19 pandemic crisis creates many hardships in organizations and unlocks numerous opportunities for organizational growth. Innovation is an essential aspect of creating a sustainable future, and it depends on the individual innovative behaviour in the organization. Although there are many opportunities to innovate, not all schools can accomplish it. School leaders are expected to overcome gaps in digitizing school systems and learning processes. This study aims to measure the positive effect of digital transformational leadership and creative self-efficacy on innovative behaviour with perceived organizational support as a mediator. The 25 items of the questionnaire were distributed to 104 teachers and employees at a XYZ school in Tangerang. Data were processed and analyzed using PLS-SEM method. The results indicated that digital transformational leadership and creative self-efficacy positively affected innovative behaviour. The results also show that perceived organizational support as a mediating variable positively affects innovative behaviour.